Big Data 29th British National Conference on databases, BNCOD 2013, Oxford, UK, July 8-10, 2013. Proceedings - Olteanu, Dan; Gottlob, Georg; Schallhart, Christian (Information Systems and Applications, incl. Internet/Web, and HCI, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 29th British National Conference on Databases, BNCOD 2013, held in Oxford, UK, in July 2013. The 20 revised full papers, presented together with three keynote talks, two tutorials, and one panel session, were carefully reviewed and selected from 42 submissions. Special focus of the conference has been "Big Data" and so the papers cover a wide range of topics such as query and update processing; relational storage; benchmarking; XML query processing; big data; spatial data and indexing; data extraction and social networks.